The Effect of Affective Commitment on the Trust of Knowledge Transfer for Family Businesses in Universitas Ciputra - Saputra, Ignatius Teddy (Universitas Ciputra Surabaya, 2022)
This study aims to explore the effect of commitment on the trust of knowledge transfer.The study is conducted using quantitative method on 50 the next generation of family businesses inUniversitas Ciputra. The study result indicates that commitment and trust simultaneously but notpartially affect knowledge transfer. This study suggests the role of knowledge transfer may determinethe success of family business across generation.